1996
DOI: 10.1080/0144341960160207
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Conductive Education in Australia: a question of programme transplantation

Abstract: This paper is concerned with issues arising from the transfer of educational programmes developed in one educational context to another, in some cases markedly different, educational situation. The introduction to Australia of conductive education, an integrated education and therapy programme developed in Hungary in the 1950s for children with physical disabilities, is an example of such a transfer. Results derived from two evaluation studies of conductive education projects in New South Wales suggest that, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…Some of the main questions arising from the two studies reported here were reviewed in Bochner et al (1996). These included issues arising from the transfer of an educational program developed in one social and cultural context to another, the effectiveness of the teacher/therapist model exemplified in the role of the conductor and differences in educational provision for students with special learning needs in Hungary and Australia.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the main questions arising from the two studies reported here were reviewed in Bochner et al (1996). These included issues arising from the transfer of an educational program developed in one social and cultural context to another, the effectiveness of the teacher/therapist model exemplified in the role of the conductor and differences in educational provision for students with special learning needs in Hungary and Australia.…”
Section: Discussionmentioning
confidence: 99%
“…Some illustrations of this point are available in the current issue. Bochner et al (1996) present a descriptive account of the difficulties that arise in attempting to transplant a programme (in this case, conductive education) from one social and cultural context to a quite different context where it is not consistent with prevailing values and views on educational practice. Widdowson, Dixon and Moore's paper (1996) on the effects of teacher modelling of silent reading on high-, average-and low-achieving students' reading behaviour provides a salient reminder that strategies that are appropriate to some students, may not be effective with others.…”
Section: Appropriate Technology For Instructionmentioning
confidence: 96%
“…Conductorn framhålls i själva verket som den största skillnaden mellan CE och andra arbetssätt ). Konsekvensen av att en person är »allt-i-allo« med kunskap inom skilda discipliner som specialpedagogik, logopedi, arbetsterapi, psykologi och sjukgymnastik diskuteras (Bochner & Center 1996). Oavsett ståndpunkt bör träningsansvaret redovisas i projekten.…”
Section: Vem Leder Och Genomför Programmet?unclassified